2014
DOI: 10.1038/bmt.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Use of G-CSF to hasten neutrophil recovery after auto-SCT for AML is not associated with increased relapse incidence: a report from the Acute Leukemia Working Party of the EBMT

Abstract: Application of G-CSF in AML is controversial as leukemic blasts may express receptors interacting with the cytokine, which may stimulate leukemia growth. We retrospectively analyzed the impact of G-CSF use to accelerate neutrophil recovery after auto-SCT on outcome. Adults with AML in first CR autografted between 1994 and 2010 were included. Nine hundred and seventy two patients were treated with G-CSF after auto-SCT whereas 1121 were not. BM and PB were used as a source of stem cells in 454 (22%) and 1639 (78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As demonstrated in a series of prospective and retrospective investigations, the above 3 factors reflect the most important general predictors of outcome in patients with AML, and are still important in the long-term follow-up. [1][2][3][4][5][6]9,18,19 In the current study, the use of PB as a source of stem cells was associated with a higher RI and inferior LFS compared with when BM was used. The role of the stem cell source was demonstrated in previous European Society for Blood and Marrow Transplantation studies by Gorin et al, in which patient outcome was analyzed from the day of auto-SCT.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…As demonstrated in a series of prospective and retrospective investigations, the above 3 factors reflect the most important general predictors of outcome in patients with AML, and are still important in the long-term follow-up. [1][2][3][4][5][6]9,18,19 In the current study, the use of PB as a source of stem cells was associated with a higher RI and inferior LFS compared with when BM was used. The role of the stem cell source was demonstrated in previous European Society for Blood and Marrow Transplantation studies by Gorin et al, in which patient outcome was analyzed from the day of auto-SCT.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, the prognostic significance of cytogenetics was apparent in a univariate analysis, and karyotype risk groups were strongly associated with FAB subtypes. As demonstrated in a series of prospective and retrospective investigations, the above 3 factors reflect the most important general predictors of outcome in patients with AML, and are still important in the long‐term follow‐up …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36 Using the same regimen, researchers in Nanjing Relevant to this study, an EBMT retrospective analysis showed that the use of G-CSF after ASCT is not associated with an increased risk of relapse. 39 The BEAM regimen has been recently advocated for T-cell ALL by the Russian ALL study group, 40 and treatment with TKI for Ph In vivo purging, MRD quantification and graft quality In the past decade numerous studies on adults and children with AML or ALL have reported that patients who achieve CR1, with no detectable MRD 41 evaluated after induction or conventional consolidation, have a significantly better outcome compared with MRD-positive patients. It is generally recommended that patients who are MRD-positive should be considered for allo-HSCT.…”
mentioning
confidence: 99%